2011
DOI: 10.1152/ajpheart.00513.2011
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase LSD1 deficiency during high-salt diet is associated with enhanced vascular contraction, altered NO-cGMP relaxation pathway, and hypertension

Abstract: Histone methylation, a determinant of chromatin structure and gene transcription, was thought to be irreversible, but recent evidence suggests that lysine-specific demethylase-1 (LSD1, Kdm1a) induces demethylation of histone H3 lysine 4 (H3K4) or H3K9 and thereby alters gene transcription. We previously demonstrated a human LSD1 phenotype associated with salt-sensitive hypertension. To test the hypothesis that LSD1 plays a role in the regulation of blood pressure (BP) via vascular mechanisms and gene transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 46 publications
(71 reference statements)
6
60
0
Order By: Relevance
“…This result is consistent with previous studies in humans, where low renin hypertensives hyperexcreted a salt load in contrast to normotensives or non-modulating hypertensives (a normal renin form of salt-sensitive hypertension) (Cottier et al 1958;Krakoff et al 1970;Luft et al 1977;Rydstedt et al 1986;Hollenberg et al 1986). In this study (data not shown) and previously (Pojoga et al 2011b), renin and aldosterone levels were suppressed in LSD1-deficient mice on HS diet, indicating that activation of the RAS is not a driving force for elevated blood pressure. As the renal vascular response is a major determinant for the ability to handle a Na + load, and LSD1 +/− mice showed enhanced vasoconstriction and impaired vasorelaxation when challenged with HS (Pojoga et al 2011b), early exaggerated natriuresis is thought to be an indicator of altered renal vascular function, which could contribute to the development of hypertension though the exact mechanisms remain unknown.…”
Section: Animal Studiessupporting
confidence: 93%
See 3 more Smart Citations
“…This result is consistent with previous studies in humans, where low renin hypertensives hyperexcreted a salt load in contrast to normotensives or non-modulating hypertensives (a normal renin form of salt-sensitive hypertension) (Cottier et al 1958;Krakoff et al 1970;Luft et al 1977;Rydstedt et al 1986;Hollenberg et al 1986). In this study (data not shown) and previously (Pojoga et al 2011b), renin and aldosterone levels were suppressed in LSD1-deficient mice on HS diet, indicating that activation of the RAS is not a driving force for elevated blood pressure. As the renal vascular response is a major determinant for the ability to handle a Na + load, and LSD1 +/− mice showed enhanced vasoconstriction and impaired vasorelaxation when challenged with HS (Pojoga et al 2011b), early exaggerated natriuresis is thought to be an indicator of altered renal vascular function, which could contribute to the development of hypertension though the exact mechanisms remain unknown.…”
Section: Animal Studiessupporting
confidence: 93%
“…In this study (data not shown) and previously (Pojoga et al 2011b), renin and aldosterone levels were suppressed in LSD1-deficient mice on HS diet, indicating that activation of the RAS is not a driving force for elevated blood pressure. As the renal vascular response is a major determinant for the ability to handle a Na + load, and LSD1 +/− mice showed enhanced vasoconstriction and impaired vasorelaxation when challenged with HS (Pojoga et al 2011b), early exaggerated natriuresis is thought to be an indicator of altered renal vascular function, which could contribute to the development of hypertension though the exact mechanisms remain unknown.…”
Section: Animal Studiessupporting
confidence: 68%
See 2 more Smart Citations
“…33 Histone H3K4 methylation and LSD1 are considered as essential epigenetic targets in cancer cells, 34 and LSD1-mediated histone demethylation is associated with hypertension and enhanced vascular contraction. 35 LSD1 specifically demethylates mono-or dimethylated H3K4 and H3K9, and removal of methyl groups from H3K4 is linked with transcriptional repression. 20 High glucose exposure of human aortic microvascular endothelial cells, in addition to increasing methylation of H3K4 and hypomethylation of H3K9, also increases the recruitment of LSD1 at the promoter of p65 subunit of NF-kB, and this is considered as one of the mechanisms associated with the activation of NF-kB.…”
Section: Discussionmentioning
confidence: 99%